REPRESENTATION OF Q.S. Al-BAQARAH [2]: 195 ON INSTAGRAM ACCOUNT @ALMUHAJIRINWALANSHAR: A PERSPECTIVE OF JEAN BAUDRILLARD’S CONSUMERISM THEORY - Desy Amelia Putri; Alin Zata Amni; Sahrul A. Poipesi (Sekolah Tinggi Agama Islam Sadra, 2025)
On 29 December 2024, the account @almuhajirinwalanshar posted a snippet from Q.S. Al-Baqarah [2]: 195, but the interpretation presented in the post was not consistent with the overall meaning of the verse. It’s because the post represented an invitation to do good deeds, even if they seem futile, by quoting the final part of QS. Al-Baqarah: 195, whereas the meaning of the verse is not as simple as discussing an invitation to do good deeds. The Instagram @almuhajirinwalanshar uses the final part of Q.S. Al-Baqarah [2]: 195 to encourage doing good deeds that feel futile, when in fact the main interpretation of the verse, according to several interpretations, focuses on the command to spend wealth for obedience, especially in the context of jihad or war, and the encouragement to do good deeds in general. Therefore, this paper aims to examine the representation of Q.S. Al-Baqarah [2]: 195 on the Instagram account @almuhajirinwalanshar using Jean Baudrillard’s consumerism theory framework. The purpose of this study is to analyze how the verse is represented on the account @almuhajirinwalanshar and how religious messages are constructed as symbols or signs in digital consumer culture. This study uses a qualitative-descriptive method through a literature review, with the main source being the account’s post content and secondary sources being literature related to Baudrillard’s theory and the interpretation of the verse. The results show that posts with the quote “Tetaplah Baik Meski Rasanya Sia-Sia” and the verse from Q.S. Al-Baqarah [2]: 195 have undergone a shift in meaning from the context of jihad to personal emotional motivation through visual, audio, and narrative aesthetics. In conclusion, social media has shaped a new interpretation of Qur’anic verses through the process of simulation and simulacra, making them objects of spiritual consumption that no longer represent their original meaning, but rather symbols of religious lifestyles in digital consumer society.